Analisis Pesan Dakwah Di Acara Mutiara Ramadhan Di TVKU Semarang - Dedi Rismanto (Sekolah Tinggi Agama Islam Publisistik Thawalib Jakarta, 2021)
Television as a very effective medium in spreading da'wah and the most influential in shaping attitudes and personality broadly, many programs on TVKU Semarang made the author choose the Mutiara Ramadhan program, one of these events is a special program that inspires and educates many people, the event was five speakers competent in their field. In this study, the researcher used content analysis theory, which was used to analyze the video content of Mutiara Ramadhan and took the da'wah messages from the text and compared it using the Qur'an, Hadith, and the opinions of the figures. The results of this study are as follows: (1) The message of da'wah in the Mutiara Ramadhan program on TVKU Semarang includes: in the Maesaroh episode there is a message of death, practicing patience. Then in the Iswatun Khasanah episode there is a message, try, be grateful. Siti Maemunah which contains the message of Islam rahmatan lil alamin, Tolerance, Bhineka Tunggal Ika. Umi Nu'ammah there is a message of sidiq, trust, help, Istiqomah. Muta'allimah contained messages about health, magfirah and the night of lailatul qadar, and (2) The da'wah method used in the Mutiara Ramadhan program on TVKU Semarang, researchers found the methods used were the Bil-lisan, Muidzah-Hasanah and Bil wisdom methods.